2008
DOI: 10.1126/science.1157774
|View full text |Cite
|
Sign up to set email alerts
|

Eco1-Dependent Cohesin Acetylation During Establishment of Sister Chromatid Cohesion

Abstract: Replicated chromosomes are held together by the chromosomal cohesin complex from the time of their synthesis in S phase onward. This requires the replication fork-associated acetyl transferase Eco1, but Eco1's mechanism of action is not known. We identified spontaneous suppressors of the thermosensitive eco1-1 allele in budding yeast. An acetylation-mimicking mutation of a conserved lysine in cohesin's Smc3 subunit makes Eco1 dispensable for cell growth, and we show that Smc3 is acetylated in an Eco1-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
573
4
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 478 publications
(610 citation statements)
references
References 28 publications
21
573
4
4
Order By: Relevance
“…Early studies had pointed out the involvement of a specialized class of acetyltransferases (Eco1/Ctf7 in budding yeast; ESCO1 and ESCO2 in vertebrates) (Ivanov et al 2002;Bellows et al 2003). A series of subsequent studies showed that two conserved residues in SMC3 are the essential targets of the Eco1/ESCO1 acetyltransferase, and the acetylation reactions are indeed essential for cohesion establishment in budding yeast (Ben-Shahar et al 2008;Unal et al 2008) and humans (Zhang et al 2008). More recently, the deacetylase that reverses this reaction has been identified as Hos1 in budding yeast (Beckouët et al 2010;Borges et al 2010;Xiong et al 2010) and HDAC8 in humans (Deardorff et al 2012).…”
Section: Cohesin Establishes Sister Chromatid Cohesion During S Phasementioning
confidence: 99%
“…Early studies had pointed out the involvement of a specialized class of acetyltransferases (Eco1/Ctf7 in budding yeast; ESCO1 and ESCO2 in vertebrates) (Ivanov et al 2002;Bellows et al 2003). A series of subsequent studies showed that two conserved residues in SMC3 are the essential targets of the Eco1/ESCO1 acetyltransferase, and the acetylation reactions are indeed essential for cohesion establishment in budding yeast (Ben-Shahar et al 2008;Unal et al 2008) and humans (Zhang et al 2008). More recently, the deacetylase that reverses this reaction has been identified as Hos1 in budding yeast (Beckouët et al 2010;Borges et al 2010;Xiong et al 2010) and HDAC8 in humans (Deardorff et al 2012).…”
Section: Cohesin Establishes Sister Chromatid Cohesion During S Phasementioning
confidence: 99%
“…These results, along with those from our phenotypic studies, suggest that CTF7 is not required for the establishment of sister chromatid cohesion in the endosperm. In S. pombe, Eso1 becomes dispensable if Pds5 is deleted (Tanaka et al, 2001), while in S. cerevisiae, the lethality of an Eco1 deletion is suppressed by inactivation of Rad61/Wpl1 (Ben-Shahar et al, 2008). Furthermore, cohesion defects in human cells depleted of Esco1 can be rescued by codepletion of Wapl1 (Gandhi et al, 2006).…”
Section: Ctf7 Is Essential For Mitosis In the Embryo But Not In Pollementioning
confidence: 99%
“…An antiestablishment complex consisting of Wings Apart-Like protein (WAPL)/Rad61 and Pds5 is required to maintain cohesion during G2/M by stabilizing the interaction between cohesin and the chromosomes (Panizza et al, 2000;Losada et al, 2005;Gandhi et al, 2006). While the specific details of how Ctf7, WAPL/Rad61, and Pds5 function together to first establish and then maintain cohesion still need to be clarified, recent results indicate that Ctf7 acetylates conserved Lys residues in SMC3, which inhibits the antiestablishment function of the Wpl1-Pds5 complex and promotes cohesion establishment (Ben-Shahar et al, 2008;Unal et al, 2008;Zhang et al, 2008;Rowland et al, 2009;Sutani et al, 2009). Ctf7 is also involved in the postreplicative induction of cohesion induced by DNA double-strand breaks (Unal et al, 2007).…”
mentioning
confidence: 99%
“…Soon after DNA is replicated, cohesin establishes physical connections between the newly formed sister chromatids [60]. Establishment of stable cohesion further requires acetyl modifications on the DNA sensing lysines of the Smc3 head by the acetyltransferase Eco1 [6164]. This acetylation counteracts Wapl-driven cohesin release, probably by direct inhibition and/or recruitment of antagonizing factors such as sororin [37,65].…”
Section: Implications For Sister Chromatid Cohesionmentioning
confidence: 99%